Content and Connectivity in the Age of Digital Libraries - Feria, Lourdes (1998)
To talk about information technologies, we should refer to the 1960s when We began to have a little more information about computers; later, from the 90s onwards, tele-computing networks, particularly the INTERNET, began to occupy our attention and became increasingly popular. This has forced both institutions and companies to get involved not only in the handling of textual data but all kinds of presentations of information, since what the user needs to transmit today over networks is also video and audio. These are the three technological domains that make up what will constitute the Virtual University in a few years.